The reception of Harold Pinter's plays in Slovenia between 1999 and 2014 - Gavez, Urša (ELOPE (Ljubljana), 2016)
Harold Pinter started his career with a conspicuous lack of success. He faced negative critical reviews of his early works, but his typical style eventually opened doors to new worlds in modern drama. On Slovene stages, Pinter's plays also received a similarly modest welcome. The audience as well as the reviewers found his long pauses, silences and incoherent dialogue insufficiently engaging. One of the main reasons for this could have been their unfamiliarity with Pinter's style, which eventually acquired its own adjective - "Pinteresque". With time, Pinter's popularity increased more rapidly on the world stages than in Slovenia, and today this playwright is not a stranger to the Slovene theatre. This article deals with Pinter on Slovene stages as well as the popular and critical reception of his plays. The period before 1999 was thoroughly analysed by Darja Hribar, while this study is the first to focus on the decade and a half following.
Keywords: angleška dramatika; angleška književnost; gledališče; literarne študije; Pinter, Harold, 1930-2008; prevodi; recepcija; theater